2018
DOI: 10.1073/pnas.1800272115
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic amino acid production from biomass-derived intermediates

Abstract: SignificanceToday, amino acids are primarily manufactured via microbial cultivation processes, which are costly, are time consuming, and require extensive separations processes. As an alternative, chemocatalytic approaches to produce amino acids from renewable feedstocks such as bio-based sugars could offer a rapid and potentially more efficient means of amino acid synthesis, but efforts to date have been limited by the development of facile chemistry and associated catalyst materials to selectively produce α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
165
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 199 publications
(172 citation statements)
references
References 47 publications
7
165
0
Order By: Relevance
“…Applications of amino acids derivatives that can be derived from biomass α‐hydroxyl acids are particularly attractive . Consequently, we investigated the hetero‐dehydrogenation of primary amines with amino acids derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of amino acids derivatives that can be derived from biomass α‐hydroxyl acids are particularly attractive . Consequently, we investigated the hetero‐dehydrogenation of primary amines with amino acids derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other biomass, lignocellulose, which is derived from agricultural waste and forest residues, is much cheaper and more abundant. Therefore, the synthesis of fuel and chemicals with lignocellulose-derived platform molecules has been a research hotspot [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the conversion of LA to GVL can also be catalysed efficiently by noble metal catalysts under mild condition because of their excellent catalytic activity for hydrogenation. [14][15][16] It had been reported that GVL yields are more than 90% over the catalysts of Ru, Pt and Pd at 90 C. 17,18 Sudhakar et al 19 had reported that hydroxyapatite (HAP)-supported Ru catalyst exhibited 99% yield of GVL from LA by hydrogenation at 70 C and 0.5 MPa H 2 pressure. However, LA conversion decreased to below 90% when the Ru/HAP was repeatedly used for 5 times.…”
Section: Introductionmentioning
confidence: 99%